The trainee primary teacher's handbook - Dixie, Gererd (Continuum, 2009)
Provides comprehensive advice for those training to become primary teachers. This book provides guidance on: choosing the right course; preparing and applying for the course; understanding the requirements of the training course; developing effective teaching skills; and, applying for jobs in order to achieve QTS.